PROSES PENGOLAHAN GARAM DI DESA KUSAMBA, DAWAN, KLUNGKUNG DALAM PHOTOGRAPHY STORY - Yana, Sang Made Dwiki Hendri; Saryana, I Made; Raharjo, Anis (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
Kusamba Village, Dawan District, Klungkung Regency, Bali is a salt-making area that is very famous for its distinctive taste and traditional processing. These salt farming skills have been passed down from generation to generation until now. This salt farming activity is carried out in a conventional way with traditional equipment. Although the number of salt farmers is decreasing day by day, the remaining farmers are still persistent in maintaining their business to meet the economic needs of their families. The purpose of this research is to raise, promote and know the salt processing process in Kusamba Village, Klungkung Bali in story photography. Meanwhile, the benefits of this research are that it can increase knowledge, think creatively, give satisfaction to the creator and contribute references to ISI Denpasar and the public can know the process of processing salt in Kusamba Village, Klungkung Bali. In this study used the method of observation, interviews, literature study. Meanwhile, to analyze the work, aesthetic theory is used, namely: idetional and technical levels and EDFAT theory. This research produced 15 story photography works that explain the process of processing salt in Kusamba Village, Klungkung Bali from sand selection, watering sand with sea water, drying, sand distillation, drying under the sun, crystallization, dredging salt grains, salt packaging and marketing processes. Meanwhile, how to visualize it can be concluded from the existence of internal and external factors in the application of ideas, observations, literature studies, photo shoots, selection, image processing, printing and exhibitions.